Minding the treatment gap: results of the Singapore Mental Health Study - Subramaniam, Mythily; Abdin, Edimansyah; Vaingankar, Janhavi Ajit; Shafie, Saleha; Chua, Hong Choon; Tan, Weng Mooi; Tan, Kelvin Bryan; Verma, Swapna; Heng, Derrick; Chong, Siow Ann (Social Psychiatry and Psychiatric Epidemiology, 2020)
Purpose To establish the 12-month treatment gap and its associated factors among adults with mental disorders in the Singapore resident population using data from the second Singapore Mental Health Study and to examine the changes since the last mental health survey conducted in 2010. Methods 6126 respondents were administered selected modules of the Composite International Diagnostic Interview, to assess major depressive disorder (MDD), dysthymia, bipolar disorder, generalized anxiety disorder (GAD), obsessive compulsive disorder (OCD) and alcohol use disorder (AUD) (which included alcohol abuse and dependence). Past year treatment gap was defined as the absolute difference between the prevalence of a particular mental disorder in the past 12 months preceding the interview and those who had received treatment for that disorder. Results The prevalence of overall 12-month treatment gap in this population was high (78.6%). A multiple logistic regression analysis revealed significantly higher odds of treatment gap among those diagnosed with OCD (compared to those with MDD) and in those with a comorbid chronic physical disorder; while those who had primary education and below and those who were unemployed were less likely to have a treatment gap as compared to those with post-secondary education and those employed, respectively. Conclusions The high treatment gap in the population is concerning and highlights the need to promote help-seeking and uptake of treatment. Given the unique demographic characteristics, i.e., those with higher education and employed were more likely not to seek treatment, targeted interventions in the educational and workplace settings should be implemented.